Jquery 1.4 reference guide. - Swedberg, Karl (Packt, 2010)
A comprehensive exploration of the popular JavaScript library Quickly look up features of the jQuery library Step through each function, method, and selector expression in the jQuery library with an easy-to-follow approach Understand the anatomy of a jQuery script Write your own plug-ins using jQuery's powerful plug-in architecture In Detail To make optimal use of jQuery, it's good to keep in mind the breadth of capabilities it provides. You can add dynamic, interactive elements to your sites with reduced development time using jQuery. If you are looking for a comprehensive reference guide to this popular JavaScript library, this book is for you. Revised and updated for version 1.4 of jQuery, this book offers an organized menu of every jQuery method, function, and selector. Each method and function is introduced with a summary of its syntax and a list of its parameters and return value, followed by a discussion, with examples where applicable, to assist in getting the most out of jQuery and avoiding the pitfalls commonly associated with JavaScript and other client-side languages. In this book you will be provided information about the latest features of jQuery that include Sizzle Selector, Native event delegation, Event triggering, DOM manipulation, and many more. You won't be confined to built-in functionality, you'll be able to examine jQuery's plug-in architecture and we discuss both how to use plug-ins and how to write your own. If you're already familiar with JavaScript programming, this book will help you dive right into advanced jQuery concepts. You'll be able to experiment on your own, trusting the pages of this book to provide information on the intricacies of the library, where and when you need it. This book is a companion to Learning jQuery 1.3. Learning jQuery 1.3 begins with a tutorial to jQuery, where the authors share their knowledge, experience, and enthusiasm about jQuery to help you get the most from the library and to make your web applications shine. jQuery 1.4 Reference Guide digs deeper into the library, taking you through the syntax specifications and following up with detailed discussions. You'll discover the untapped possibilities that jQuery 1.4 makes available, and polish your skills as you return to this guide time and again. In this book, the creators of the popular jQuery learning resource, learningquery.com, share their knowledge, experience, and enthusiasm to bring you a comprehensive reference to this popular ...